Ocean tides and the influence of sea‐level rise on floods in urban areas of the Mekong Delta. Issue 4 (14th January 2014) - Takagi, H.; Ty, T.V.; Thao, N.D.; Esteban, M.
Abstract: The present paper investigates fluvial flood hazards in urban areas in the Mekong Delta to inundation due to seasonal flooding, a phenomenon which is likely to be exacerbated by future sea‐level rise. Unlike past researches which mainly focus on flooding due to river discharge from upstream or heavy precipitation, the present paper scrutinises the influence of ocean tides. The research reveals that ocean tides predominantly determine water elevation even in an upstream location such as Can Tho City, 80 km inland from the river mouth, and that the river flow causes tidal damping and effectively reduces the energy of the incoming tides. This tidal damping is especially pronounced during the rainy season. Analysis based on the water levels monitored by the Mekong River Commission revealed that the ground near the riverbank of Can Tho had experienced inundation for a total of 215 h between July 2009 and June 2010 (2.5% of the time over a 1‐year period). Assuming three scenarios of sea‐level rise of 20, 40, and 60 cm, all within the range of the Intergovernmental Panel on Climate Change (IPCC) AR4's projections, it was found that the duration of inundation will be prolonged from the present percentage of 2.5% to 6%, 13%, and 24% of the year, respectively. Furthermore, the field survey carried out by the authors shows that inundation reached up to a height of 47 cm above the roads of Can Tho downtown.